Performance Investigation of Cylindrical Double Gate Junctionless FET - Singh B.; Jit S. (My University, 2025)
The paper proposes a TCAD simulation based comparative study of cylindrical double gate junctionless (CDGJLFETs) and cylindrical single gate junctionless FETs (CSGJLFETs). The CDGJLFETs show better results than CSGJLFETs in terms of subthreshold current, channel potential, threshold voltage roll off, subthreshold swings and analog parameters due to better control of gates over the channel. © 2018 IEEE.